Shocked by Therapy? Unemployment in the First Years of the Socio-Economic Transition in Poland and its Long-Term Consequences - Michal Myck; Monika Oczkowska (Institute of Labor Economics (IZA), 2018)
We examine long-term implications of unemployment for material conditions and well-being using the Polish sample from the Survey of Health, Ageing and Retirement in Europe (SHARE). Retrospective data from the SHARELIFE survey are used to reconstruct labour market experiences across the threshold of the socio-economic transformation from a centrally planned to a free market economy in Poland. These individual experiences are matched with outcomes observed in the survey about 20 years later to examine their correlation with unemployment at the time of the transition. We find that becoming unemployed in the early 1990s correlates significantly with income, assets and a number of measures of well-being recorded in 2007 and 2012. Using plant closures to reflect exogenous changes to labour market status at the time of the transition, we are able to confirm the causal effect of unemployment on income and house ownership 20 years later, but find no evidence for a long-term causal relationship between unemployment and such measures of well-being as life satisfaction, depression and subjective assessment of material conditions.
Keywords: J21; J63; P30; 330; economic transition; unemployment; life histories; long-term effects